Effects of self-selected dehydration and meaningful rehydration on anaerobic power and heart rate recovery of elite wrestlers - Cengiz, A. (Journal of Physical Therapy Science, 2015)
[Purpose] This study aimed to verify the effects of self-directed weight loss on lower- and upper-body power, fatigue index, and heart rate recovery immediately before a meaningful competition (12 hours of recovery). In addition, this study tested the hypothesis that weight loss provides advantages in strength and power, as the relative power of the wrestlers is higher than that of opponents in the same weight class who do not reduce weight. [Subjects and Methods] Eleven well-trained wrestlers volunteered for the study. At baseline, their mean ± SD age, body mass, and height were 20.45 ± 2.69 years, 74.36 ± 9.22 kg, and 177 ± 5.71 cm, respectively. Repeated-measures one-way analysis of variance was performed to analyze differences. [Results] Rapid weight loss achieved by restriction of energy and fluid intake resulted in exercise-impaired decreases in peak power and increased fatigue index. Moreover, weight loss by dehydration negatively affected cardiovascular stability. [Conclusion] Most of the negative effects of rapid weight loss disappear after a 12-hour recovery period, and relative peak power increases after weight loss.